Minimal effects of the 2014-16 marine heatwave on fish assemblages found in eelgrass meadows on the southwestern coast of Vancouver Island, British Columbia, Canada - Robinson, Clifford L.K.; Yakimishyn, Jennifer; Evans, Rhian (Frontiers in Marine Science, 2022)
The main objective of this study was to ascertain if the 2014 to 2016 spring marine heatwave, anomalously high water temperatures, had a significant effect on early summer fish assemblage species composition, abundance or biomass in nursery eelgrass meadows. It was presumed that increased water temperatures above the 90th percentile of the 30y long-term spring temperatures would result in changes to fish growth, survival and ultimately leading to changes in early summer settlement to eelgrass. We assessed this by analyzing the catch per unit effort of 18 common fish species and total fish assemblage biomass in 22 eelgrass meadows from two study areas in the northern California Current during the early summer of each year from 2004 to 2021. A control chart analysis indicated that eelgrass fish assemblages during heatwave years (2015-16) were significantly higher than the 90th percentile in Bray Curtis dissimilarity of 13 baseline years. Furthermore, analysis of similarity indicated that 16 of 18 fish species showed variable contributing increases or decreases in catch per unit effort during the heatwave period. However, there were no detectable changes in eelgrass fish species composition or assemblage level biomass during the heatwave years. An analysis of the temporal trajectory over the 17y time series in the ordination plots also revealed that changes in fish assemblage dissimilarity as a result of variations in catch during the 2015 and 2016 heatwave returned quickly to levels observed during baseline. Altogether, the results of this study suggest that while the short-term spring heatwaves (34-42 d) resulted in changes in some early summer fish species abundances, these changes were short-lived. Hence, our results warrant caution about generalizing about the effects of heatwaves on nearshore marine fish.